(untitled) (Innovaciones Educativas, 2021)
In this essay, humanistic education is recognized as a pertinent strategy for university higher education. Humanistic education is one of the fundamental aspects for the training process at the higher level to achieve a fairer society. Therefore, when working with the student body, it is necessary to apply educational methods that teach a person to have a certain code of conduct with himself and others. Papalia, Martorell and Feldman (2006) point out the need to recognize respect for the rules in order to establish a just and participatory society. For the future of education, it is necessary to recover the focus of humanistic training at the university. Humanism is conceived as a select process for the establishment of relationships that are more human, dialogic transformations and collaboration methods, through the collective exercise between peers and certainly with the invaluable help of the teachers. It is necessary that this humanistic idea of education be reflected in the daily life of the school classroom. It is not intended to be a theory analyzed by the academia of university professors, but rather this approach is carried out in a practical way in each relationship or interaction of the teaching staff with their students. In addition, education in values is analyzed as a fundamental element at this time. Comprehensive education is a pedagogical peculiarity in all processes of human education.